A Pre- and Post-Pandemic Analysis of Sales Growth, Leverage, and Intellectual Capital as Determinants of Financial Distress in Property & Real Estate - Akbar, Taufik; Pratiwi, Esti Utami (Review of Accounting and Taxation, 2024)
Purpose - This study aims to investigate the impact of sales growth, leverage, and intellectual capital on financial distress in the property and real estate sub-sector, comparing the periods before and after the onset of the COVID-19 pandemic Design/methodology/approach - The study employs a quantitative research design using panel data regression analysis. Financial data from listed property and real estate companies in Indonesia will be collected for the periods before (2017-2019) and after (2020-2022) the onset of the COVID-19 pandemic. The Altman Z-score will be used as a proxy for financial distress. Sales growth, leverage ratios, and intellectual capital (measured using the VAIC model) will serve as independent variables, with profitability as a moderating variable. Comparative analysis between the pre- and post-pandemic periods will be conducted to identify any significant changes in the relationships between the variables. Finding - Findings indicate that sales growth does not impact financial distress; leverage has a significantly negative effect, while intellectual capital has a notably positive effect. Additionally the COVID-19 pandemic has had a profound impact on the companies under study, resulting in a statistically significant difference in sales growth, intellectual capital, profitability, and financial distress between the pre- and post- pandemic periods Originality -It provides a comprehensive analysis of financial distress determinants in the property and real estate sub-sector, an area that has been underexplored in existing literature